Creative Youth: A systematic review of outcomes and trends in Phase One of the Creative Youth Plan. Insights and Implications - An Interim Report - O'Sullivan, Carmel (Creative Ireland Programme, 2022)
The following interim report presents findings on creative activity among children and young people in Ireland using data from reports submitted during Phase One of Creative Youth. Using a programme logic model (i.e., linking activities with inputs, outputs, impacts) to organise data from the systematic review process, we investigated what can be learnt from the available data at the time of this study (cut off point April 2022). 26 reports met the inclusion criteria and allowed us to explore a broad selection of arts-based and creative activities. A ‘close reading’ approach was used to classify and code information extracted from reports along the following axes: inputs, activities, outputs and expected/unexpected outcomes. In addition, we undertook an extensive literature review to provide an overview of creative engagement on a national and international level, exploring its impact on individual and community well-being, social cohesion and as a strategy for economic development. We engaged with broader research studies relevant to Creative Youth, such as Growing Up in Ireland (GUI), research from the Economic and Social Research Institute (ESRI) into arts and cultural participation of young people in Ireland, and research reports from The Arts Council. The research examines if common trends were identifiable across reports, specifically in relation to achieving the key objectives of Creative Youth. Using the data available we looked for evidence of creative engagement, the voice of children and young people, inclusivity, collaboration, innovation, increasing access to seldom heard groups, evaluation, and sustainable outcomes. These findings detail the importance of capturing data through using robust evaluation mechanisms and flexible approaches to research in the arts and creative sectors. The data were incomplete in several areas, for example, just over 30% of reports described sample size, and in most, demographic details were limited or missing, with little/no information on gender, age or socio-economic status. In many, there was little/no detail about research/evaluation design. Owing to a level of underreporting in most reports, ‘granular’ and extensive analyses were applied to address challenges posed. Using the data, we investigated the extent and nature of children’s and young people’s involvement in creative activities during Phase One of Creative Youth. These findings detail the importance of the Creative Youth Plan in driving personal and collective creativity, and its impact on individual and societal wellbeing and development through both sustained and one off smaller scale initiatives and larger scale projects such as Cruinniú na nÓg. These findings present insight into informing the objectives of the second Creative Youth Plan and provide foundations for future, more in-depth research on involvement, motivations, and barriers to participation.
Routledge Handbook on Arts and Global Development
Keywords: Arts Education; Arts in Education; Drama and theatre in education; Educational Evaluation/Assessment